Taiwan Goverments Responsibility For The Provision of Public Facilities Detrimental To The Community - Muhammad Afif Hidayatulloh; Rafiqi Anjasmara; Imaniar Imaniar (Jurnal Ilmu Sosial Mamangan, 2019)
This article aims to analyze Taiwan's government accountability for fishermen who are working in the waters of Nanfangao, Taiwan. Jeremy Bentham through his book "Introduction to the morals and legislation" states that legal duty is nurturing goodness and preventing evil, so the law should provide benefits or usability for the crowd (to serve Utili TY). The community as a basic component can sue the government if in other cases raises losses on the management of public facilities and infrastructure. It also relates to the Taiwan government's liability for legal protection, for which the state's responsibility has been regulated in the SCL (State Compensation Law) or the Taiwan State Compensation Act. As for that would be a case study of bridge collapse which is one of the disability management of state-owned public facilities that cause harm to the community in Taiwan. That article 2 SCL describes the country or Government of Taiwan shall be liable for any form of loss, property damage and loss of life arising from the management of the state's public facilities. This is a real example of the application of Taiwan's accountability to public services as a form of legal protection to the public. The concept of the responsibility in Indonesia is governed by article 1365 BW, that personal accountability is caused by individual events and legal acts. There is a comparative study of government and local Government accountability within the scope of administrative law..